Multi-level Governance Conceptual Challenges and Case Studies from Australia - A. Daniell, Katherine; Kay, Adrian (Australia and New Zealand School of Governance (ANZSOG), 2018)
Important policy problems rarely fit neatly within existing territorial boundaries. More difficult still, individual governments or government departments rarely enjoy the power, resources and governance structures required to respond effectively to policy challenges under their responsibility. These dilemmas impose the requirement to work with others from the public, private, non-governmental organisation (NGO) or community spheres, and across a range of administrative levels and sectors. But how? This book investigates the challenges-both conceptual and practical-of multi-level governance processes. It draws on a range of cases from Australian public policy, with comparisons to multi-level governance systems abroad, to understand factors behind the effective coordination and management of multi-level governance processes in different policy areas over the short and longer term. Issues such as accountability, politics and cultures of governance are investigated through policy areas including social, environmental and spatial planning policy. The authors of the volume are a range of academics and past public servants from different jurisdictions, which allows previously hidden stories and processes of multi-level governance in Australia across different periods of government to be revealed and analysed for the first time.